Tuning of physical properties of Van Der Waals bonded materials through charge transfer - Hu, Peng (2017)
Organic semiconductors are attractive for electronics applications due to soluble process, low cost and large area processing. Compared with polycrystalline materials, single crystals allow investigation of intrinsic properties and relationship between molecular packing and properties, due to nearly perfect structures and low concentration of structure imperfections. Charge transfer compounds, formed by molecules, exhibit electrons transfer from donor to acceptor. Such compounds show lots of special electrical properties, such as ambipolar properties, high conductivity, even superconductivity. Charge transfer compounds also show unique properties, such as ferromagnetic properties in C60-TDAE, bound states with multiple excitons in anthracene-TMDA and ferroelectrics in lock arm supramolecular ordering system. It is an effective way to tuning the physical properties through charge transfer. Perylene-TCNQ charge transfer compound single crystals with different stoichiometry were grown from solution. The stoichiometries of final perylene-TCNQ charge transfer compound depend on the using solvent, but not depend on the starting stoichiometry of perylene and TCNQ. (Perylene)1(TCNQ)1 (P1T1) is grown from toluene and (perylene)3(TCNQ)1 (P3T1) is grown from benzene, no matter what stoichiometry of perylene and TCNQ are used in the beginning. The reason for such phenomenon is that the crystals with lower solubility will precipitate first. As a result, only P1T1 is formed from toluene because P1T1 is less soluble than P3T1 in this solvent. As P3T1 is less soluble than P1T1 in benzene, only P3T1 was crystallized from benzene. By using PVT method, a mixture of monomolecular crystals and all three charge transfer compound single crystals (P1T1, P2T1 and P3T1) are obtained. Field-effect transistors on the single crystal surfaces of P1T1, P2T1 and P3T1 have been made. The results reveal that P1T1 is typically an n-type semiconductor, P3T1 showed p-type behavior, whereas P2T1 showed ambipolar properties. From P1T1 to P3T1, the increase of perylene molecules in the unit cell may lead to the transformation of the single crystal from n-type to p-type. The methodology of searching for novel organic charge transfer binary compounds and crystal growth was made in the case that only the two starting organic substances are known but the phase diagram is not known, the thermodynamic data of the binary compound are not known and even the existence of new binary compounds is not known. Kinetically lowering the sublimation rate was the key factor for growing large-size charge transfer compound single crystals. By using this concept, crystals of novel perylene-F1TCNQ, perylene-F2TCNQ and perylene-F4TCNQ charge transfer binary compounds were obtained by decreasing the evaporation area of the individual components. Perylene-F4TCNQ shows room temperature ferromagnetism, which is undiscovered before. The larger charge transfer degree may play an important role in expressing the properties in perylene-F4TCNQ. On the other hand, the weak acceptor, TCNQ, does not cause ferromagnetism in perylene-TCNQ because the degree of charge transfer is too low. Triangle monolayer WS2 and MoS2 were grown using the chemical vapor deposition (CVD) method. The formation of the monolayers was confirmed by both AFM and Raman spectra. The PL increased after a thin layer of F4TCNQ was deposited on the surface of the WS2 and MoS2 monolayers. The reason for such an increase is the dissociation of trions. The charged excitons, trions, lose electrons during the charge transfer from monolayer WS2 and MoS2 to F4TCNQ. Meanwhile, the weaker exciton-phonon interaction of WS2 results in narrower PL peaks with larger amplitudes. Therefore, the charge transfer of electrons to the acceptor, such as F4TCNQ, from CVD-grown monolayer WS2 and MoS2 enhances the PL, and materials with weaker exciton-phonon interactions show a stronger PL intensity.